2013
DOI: 10.1007/s11356-013-1631-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transformation and dechlorination of p-chloronitrobenzene in the combined ZVI–anaerobic sludge system

Abstract: The combination of zero-valent iron (ZVI) with anaerobic sludge for enhancing reductive transformation and dechlorination of p-chloronitrobenzene (p-ClNB) was investigated in this study. p-ClNB was quickly reduced into p-chloroaniline (p-ClAn) and subsequently dechlorinated into aniline in the complex system, and the strengthening factor for pseudo-first-order transformation rate constant of p-ClNB (Q, k ZVI + sludge/(k sludge + k ZVI)) was above 3. The Q values for the different ZVI types with anaerobic sludg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Colunga et al (2015) reported high inhibitory effects and poor reduction of 3-CNB at concentration of 0.5 mM under methanogenic conditions, suggesting to apply an adequate loading rate of this type of contaminant in UASB reactors to avoid inhibition of the microbial consortia. Other studies concerning p-CNB have been reported in anaerobic conditions using zero valent iron (dosage of 1 g L −1 , for p-CNB of 0.28 mM) (Zhu et al 2013) and a novel bioelectrode-UASB coupled system (99 % removal of p- Fig. 4 Proposed pathway of iopromide degradation and transformation products CNB with transformation rate of 0.328 h −1 for concentration 0.19 mM) (Zhu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Colunga et al (2015) reported high inhibitory effects and poor reduction of 3-CNB at concentration of 0.5 mM under methanogenic conditions, suggesting to apply an adequate loading rate of this type of contaminant in UASB reactors to avoid inhibition of the microbial consortia. Other studies concerning p-CNB have been reported in anaerobic conditions using zero valent iron (dosage of 1 g L −1 , for p-CNB of 0.28 mM) (Zhu et al 2013) and a novel bioelectrode-UASB coupled system (99 % removal of p- Fig. 4 Proposed pathway of iopromide degradation and transformation products CNB with transformation rate of 0.328 h −1 for concentration 0.19 mM) (Zhu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not report dehalogenation efficiency. Removals of p-chloronitrobenzene in bioreactors seeded with anaerobic sludge in combination with ZVI were higher than those of control bioreactors with only anaerobic sludge (increase of 47 %, compared to sludge control; Zhu et al 2013). The experiments were performed in batch small reactors (serum bottles, 100 mL), inoculated with anaerobic sludge (1.5 g of volatile suspended solids (VSS)/L, previously acclimated to the pollutant) from a municipal wastewater plant and loaded with 5 g/L ZVI 22 mm average diameter.…”
Section: Introductionmentioning
confidence: 81%
“…Chloroanilines are widely used for the industrial synthesis of pesticides, plastics and dyes 1,2 . Thus, chloroanilines may be released into the environment directly during transportation and industrial processing or indirectly from the anaerobic biotransformation of many pesticides and dyes 2,3 . It is well known that the dechlorination and subsequent degradation of chloroanilines are slow processes under anaerobic conditions 2,4 .…”
Section: Introductionmentioning
confidence: 99%